2018
DOI: 10.1089/wound.2017.0775
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipose-Derived Stem Cell Conditioned Media and Exosomes Containing MALAT1 Promote Human Dermal Fibroblast Migration and Ischemic Wound Healing

Abstract: Objective: Chronically ill patients heal recalcitrant ulcerative wounds more slowly. Human adipose-derived stem cells (hADSCs) play an important role in tissue regeneration and exosomes secreted by hADSC contribute to their paracrine signaling. In addition to cytokines, lipids and growth factors, hADSC secrete mRNA, miRNA, and long noncoding (lnc) RNA into exosomes. In this study we examined the role of lncRNA MALAT1 (metastasis-associated lung adenocarcinoma transcript 1), an abundant lncRNA in exosomes from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(131 citation statements)
references
References 37 publications
7
114
0
2
Order By: Relevance
“…Also, it has been shown that conditioned media from human adipose-derived stem cell (ADSC) cultures stimulated both the human dermal-fibroblast migration and closure of ischemic wounds in a rat model. That is due to the presence of long ncRNA (lncRNA) of metastasisassociated lung-adenocarcinoma transcript 1 (MALAT-1) in EV (Cooper et al, 2018).…”
Section: Skin Wound Healingmentioning
confidence: 99%
“…Also, it has been shown that conditioned media from human adipose-derived stem cell (ADSC) cultures stimulated both the human dermal-fibroblast migration and closure of ischemic wounds in a rat model. That is due to the presence of long ncRNA (lncRNA) of metastasisassociated lung-adenocarcinoma transcript 1 (MALAT-1) in EV (Cooper et al, 2018).…”
Section: Skin Wound Healingmentioning
confidence: 99%
“…In this study, ASC-CM was prepared by incubating ASCs with serum-free DMEM for 24 h. No details on the concentration of the CM used were provided by the authors. In another study [61], ASC-CM, previously collected from ASCs cultured for 48 h in serum-free MSC basal medium, was shown to stimulate HDF migration in vitro by 43% when compared to untreated cells as analyzed through a scratch and electric cell-substrate impedance assays. To investigate the underlying molecular mechanisms driving the therapeutic impact of the ASC-secretome, Park et al [46] used CM samples collected from cultured ASCs previously isolated from adipose tissues of breast cancer patients.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…The evaluation of lesions at day 0, 2, 5, and 10 indicated that ASC-secretome treatment was able to stimulate skin thickening, angiogenesis, and recruitment of immune cells, thus accelerating the wound healing process. Using a rat model of an ischemic wound (Fisher 344 rats, full-thickness excisional wounds created with a 6 mm punch biopsy), Cooper et al [61] reported that ASC-CM collected from ASCs cultured for 48 h in serum-free MSC basal medium and applied at 20 碌L to each wound daily significantly accelerated ischemic wound closure compared to unconditioned medium. Irons et al [68] recently showed that after topical application of CM collected from ASCs isolated from the gluteal region of Yorkshire pigs, the diabetic wound healing in the same animals was significantly enhanced, with concomitant increased angiogenesis and immunomodulation.…”
Section: In Vivo Experimental Studiesmentioning
confidence: 99%
See 2 more Smart Citations